2017
DOI: 10.12669/pjms.332.12410
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Dyslipidemia in patients with Lupus Nephritis

Abstract: Objective:To determine the frequency of dyslipidemia in patients with lupus nephritis and its association with the degree of proteinuria.Methods:This cross-sectional analytic study included 65 patients who fulfilled the ACR (American College of Rheumatology) criteria for SLE and had renal involvement, presenting to the Division of Rheumatology, Fatima Memorial Hospital (FMH), and Lahore from 21st Sep 2016 to 20th Dec 2016. After 12 hours overnight fast their blood samples were assessed for total cholesterol (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…In addition, studies have shown that the prevalence of dyslipidaemia in lupus patients ranges from 36% to 60% at the time of diagnosis, and even higher after three years. 8,17 The present study showed that a total of 21 patients (51.2%) had renal disorders. SLE patients can experience skin, kidney, haematological and musculoskeletal involvement.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In addition, studies have shown that the prevalence of dyslipidaemia in lupus patients ranges from 36% to 60% at the time of diagnosis, and even higher after three years. 8,17 The present study showed that a total of 21 patients (51.2%) had renal disorders. SLE patients can experience skin, kidney, haematological and musculoskeletal involvement.…”
Section: Discussionsupporting
confidence: 49%
“…It has also been found that dyslipidaemia is common in lupus nephritis patients and it is strongly associated with proteinuria due to the increase in lipid synthesis. 6,17 Our recent study found that the average steroid dose of subjects did not exceed 30 mg/day. However, another study found that 74% of patients had a steroid dose of less than 30 mg/day.…”
Section: Discussionmentioning
confidence: 95%
“…Sajjad et al., have found that 55.4% of lupus nephritis patients had high levels of low-density lipoprotein (LDL). 12…”
Section: Discussionmentioning
confidence: 99%
“…LN patients have higher risks for ischemic heart diseases [38,39], which is likely caused by abnormalities in lipid metabolism. It is estimated that 30-50% of LN patients have high plasma total cholesterol and LDL levels [40][41][42]. It is unclear whether elevated miR-148a would contribute to hypercholesterolemia in LN patients by affecting LDL metabolism via the (P)RR.…”
Section: Discussionmentioning
confidence: 99%